Characteristics of variegated-leaf chimera of Hosta - XIA Yi-ping; LI Qian-yu; CHANG Le; SHEN Chao-dong; LI Fang (浙江大学学报. 农业与生命科学版)
The variegated characters of Hosta is related to the stable inheritance of chimera. Hosta 'So Sweet' and H. ventricosa were selected as the materials to identify the characteristics of variegated-leaf chimera in Hosta plants, which comparing the physiological and morphological differences in various parts of their leaves. The results show that, in the yellow parts of H. 'So Sweet' variegated leaf, the contents of chlorophyll-a and total chlorophyll were significantly lower than those in other parts and in the leaf of H. ventricosa, whereas the content of chlorophyll-b showed obviously higher. An additional esterase isozymogram was found in the Hosta leaf, which probably indicated as the special esterase in variegated Hosta. Concerned different parts from green, intergraded color and yellow in variegated leaves, the aberrance phenomena in ultrastructure of chloroplasts was observed, including the roundness from ellipse, granum-thylakoid swelling, vesicle forming and osmiophilic globule increasing.